Kurikulum Pendidikan Sejarah di Amerika Serikat - Bahri Bahri (Jurnal Pendidikan Sejarah, 2015)
The Bradley is a commission created in 1987 in response to concern over the shortage , both in quantityand quality , of the teaching of history in America , both at primary and secondary school level . Indeed,before 1892, the teaching of history is considered not too concerned, but for various cases at the highschool level , forcing the National Education Association case the importance of teaching all levels ofeducation. History must have particular relevance to struggle with the problem of irreversibility timein their own lives , searching for meaning and commitment to themselves, and defines adolescents whodevelop a sense of their own past of their relationship with the community. Four patterns in the teachingof history in the teaching of history in secondary schools in the US, and the school was granted fordetermining the pattern to be used